ІНТЕРАКТИВНІ ТЕХНОЛОГІЇ НАВЧАННЯ ІНОЗЕМНИХ МОВ У ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДАХ - Koval, T (Continuing Professional Education: Theory and Practice, 2019)
The interactive technologies in teaching foreign languages in high school as a holistic and integrated system of teaching process are considered in the article. In respect of learning objectives it includes the most effi cient usage of selected interactive methods, means and forms of foreign languages learning, taking into account the principles of communicativeness, feasibility of implementing and mutual complement, in order to achieve a pre-planned (desired) result.